Prevalence and Determinants Stunting Among Children Under Two Years in Indonesian District - Fahmi Hafid; Ansar Ansar; Nasrul Nasrul; Kadar Ramadhan; Ardiansyah Ardiansyah (Poltekkes Kemenkes Palu, 2023)
The study aims to analyze the prevalence and determinants of stunting in children under two years of age in Tojo Una-Una District, Indonesia as focus location of stunting. The method is Cross-sectional study design, the sample of 300 children aged 0-23 months, stratified random sampling technique. Data collection in June-July 2022. Stunting data was obtained by measuring body length using the length measuring board. The WHO-Antro 2005 software was used to determine the Z-Score height per age. Univariate, bivariate, and multivariate analyzes used SPSS version 22.00. The Results of this research show that 33.7% of children under the age of two are stunted. Stunting in children under the age of two is associated with child age, birth weight, and food insecurity. In addition to a history of low birth weight (AOR=2.7, 95% CI: 1.2-5.7) and experiencing food insecurity (AOR=1.9, 95% CI: 1.1-3.5), children aged 12-23 months (AOR=3.5, 95% CI: 1.7-7.2) have a higher tendency to experience stunting than those who are not. The Conclusion is the prevalence of stunting which is more than 20 percent is a priority health problem that must be resolved by 2024. Interventions to reduce stunting by reducing the incidence of low birth weight, reducing food insecurity, managing birth spacing > 3 years, number of children less than 3, and breastfeeding.